Intimacy and emotions at the dawn of Performance Art in Italy. Issue 3 (August 2021) - Gallo, Francesca
Abstract : This paper investigates the actions executed by Italian artists – male and female – centred on interpersonal relationships, at times with an insight into the dynamics of couples or directly involving the public. In Italy, during the 1960s and 1970s, various artists dedicated themselves to what were initially called happenings or actions, and only later became known as 'performances', but unlike in the better-known Body Art, the phenomenological exploration of the self and of reality frequently observed in the Arte Povera circle of artists, many welcomed the new sensibility embodied by feminism, which, by redefining gender positioning, emphasised the centrality of the 'private' sphere and revived interest in 'affection'. This is particularly significant in light of the Italian cultural context, where women artists have often looked with suspicion at any initiatives dedicated explicitly to women's issues or at women-only exhibitions.